Comparative Analysis of Erbium Doped Fiber Amplifier (EDFA) and Raman Optical Amplifier (ROA) in Nonlinear-CWDM System - Dodi Zulherman; Fahmi Fahmi; Sri Utami; Tri Heru Santoso; Satria Adi Nugroho (JURNAL INFOTEL, 2018)
The massive demands for high-rate application drove the telecommunication service to use large bandwidth capacity. The Coarse Wavelength Division Multiplexing (CWDM), common use in Metro-WDM, can be a solution to provide large bandwidth in optical communications. In a communications system, there are attenuation and nonlinear effect decreasing the system performance. To overcome the limitation imposed by electrical regeneration to maintain system performance, a means of optical amplification was sought. In this paper presents the comparison of two competing technologies emerged: Erbium Doped Fiber Amplifier (EDFA) and Raman Optical Amplifier (ROA) to overcome the attenuation in the nonlinear system. We designed the CWDM system using 8 channels with 20 nm channel spacing and 60 km length. The result was conducted by varying the optical power launch using -8, -6, -4, -2, 0, 2, 4, and 6 dBm. Based on the result of the research, Raman amplification can maintain the BER and the Q-factor that meet the ITU-T standard for all optical power launch value, but EDFA can maintain those for optical power launch more than 0 dBm. In addition, the received power in Raman amplification larger than that received in EDFA. In conclusion, a CWDM system using ROA amplifier prefer to use for the system than using the EDFA amplifier.